Competency domains of educators in medical, nursing, and health sciences education: An integrative review. (1st February 2023) - Sidhu, Navdeep S.; Allen, Kara J.; Civil, Nina; Johnstone, Charlotte S. H.; Wong, Maggie; Taylor, Jennifer A.; Gough, Katherine; Hennessy, Maurice
Abstract: Purpose: Competencies for educators of healthcare professionals are important for demonstrating accountability, defining roles and responsibilities, structuring activities for training and development, defining standards, quality assurance, performance reviews, career development, and promoting the professionalisation of teaching. The frameworks and domains of educator competencies have not previously been reviewed or systematically described. Through this integrative review, the authors sought to identify an inclusive structure for competency domains that may be applied to educators. Methods: Keywords were identified in a pilot search, followed by a multi-database search strategy of records published from 2000 to January 2020 with subsequent backward and forward reference searches. We included all record types that listed or described educator competency domains in medical, nursing and health sciences education. We excluded records that described 'ideal traits' or 'characteristics of good teachers/educators, ' presented competencies as part of a larger curricular framework, and teaching assessment tool content. Results: The multi-database search retrieved 2942 initial citations. From a full-text review of 301 records, 67 were identified as describing educator competency domains eligible for analysis. Documents contained a median of six domains (interquartile range = 5–7) and 14.9% incorporated at least one overarching element across their domains. Following an inductive thematic analysis, six distinct domains of educator competence were identified: Teaching and facilitating learning; Designing and planning learning; Assessment of learning; Educational research and scholarship; Educational leadership and management; Educational environment, quality, and safety. The two latter domains contained sub-themes that were able to be further categorised. Documents and frameworks were described for a wide variety of health and allied health disciplines. Conclusion: Distinct educator competency domains were identified in this analysis, applicable across a range of healthcare disciplines. Along with the description of design elements, these provide a guide for the development and evaluation of educator competency frameworks.